'Sit in my seat': perspectives of students with learning disabilities about teacher effectiveness in high school inclusive classrooms. Issue 3 (23rd February 2020) - Connor, David J.; Cavendish, Wendy
ABSTRACT: In the USA, students with learning disabilities (LD), after students with speech and language impairments, are the second highest incidence disability category of children and youth receiving the majority of their education in inclusive classrooms. However, very few studies exist that share perspectives of school experiences by students with LD in inclusive classrooms. This qualitative study focuses upon the importance of student voice through interviews of 40 high school students with LD in 3 schools. We share our findings about specific teacher characteristics and pedagogical skills that influence student perceptions of effective and ineffective teachers. From these findings, we provide a descriptive summary of what students identify as teacher characteristics and pedagogical skills that help them learn best. Finally, we discuss the implications of our findings as related to theory, research, practice, and policy.